1975
DOI: 10.1111/j.1471-4159.1975.tb11871.x
|View full text |Cite
|
Sign up to set email alerts
|

A COMPARATIVE STUDY OF THE METABOLISM OF DE NOVO SYNTHESIZED FATTY ACIDS FROM ACETATE AND GLUCOSE, AND EXOGENOUS FATTY ACIDS, IN SLICES OF RABBIT CEREBRAL CORTEX DURING DEVELOPMENT

Abstract: Abstract— Slices of rabbit cerebral cortex, from the foetal stage to the adult have been used to compare lipid synthesis from fatty acids synthesized de novo from [U‐14C]glucose and [1‐14C]acetate, with lipid synthesis from exogenous albumin‐bound [1‐14C]palmitate. Incorporation into cellular lipid has been determined in terms of DNA, protein, wet wt. of tissue and wet weight of whole brain. On a wet wt. basis, maximum incorporation of glucose carbon into lipid occurred in the foetal brain while lipid synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…This is particularly evident in that the rates of cerebral glucose utilization, based on the uptake of 2-[ 14 C]deoxyglucose, approach 60 mol/g/h (recalculated from Brown and Lorden, 1989;Choi et al, 2001;Simpson et al, 2007). Furthermore, direct measurements in the in vitro brain slice preparation demonstrated that approximately 385 nmol/g/h of glucose is completely oxidized, which sharply contrasts with the extremely low rates of fatty acid (i.e., palmitate) oxidation, which amount only to 0.02 nmol/g/h (Carey, 1975). This suggests that fatty acids are not an important energy substrate for the brain.…”
Section: B Hypothalamic Intermediary Fuel Metabolismmentioning
confidence: 83%
See 3 more Smart Citations
“…This is particularly evident in that the rates of cerebral glucose utilization, based on the uptake of 2-[ 14 C]deoxyglucose, approach 60 mol/g/h (recalculated from Brown and Lorden, 1989;Choi et al, 2001;Simpson et al, 2007). Furthermore, direct measurements in the in vitro brain slice preparation demonstrated that approximately 385 nmol/g/h of glucose is completely oxidized, which sharply contrasts with the extremely low rates of fatty acid (i.e., palmitate) oxidation, which amount only to 0.02 nmol/g/h (Carey, 1975). This suggests that fatty acids are not an important energy substrate for the brain.…”
Section: B Hypothalamic Intermediary Fuel Metabolismmentioning
confidence: 83%
“…Nonetheless, fatty acids and their metabolites are recognized as important cellular messengers in the brain. This supposition is evinced from the extremely low rates of fatty acid ␤-oxidation observed in brain slice preparations compared with the rates of fatty acid incorporation into various intracellular lipids (Carey, 1975), as well as the low rates of fatty acid ␤-oxidation relative to fatty acid activation (i.e., esterification) in neuron-derived neuro2A cells (Pei et al, 2003). The mechanism(s) by which fatty acids and their metabolites influence the CNS, particularly the hypothalamic regulation of energy homeostasis, has become an area of intense investigation (section II.D).…”
Section: B Hypothalamic Intermediary Fuel Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data tend to confirm this, for the high pentose pathway activity which we show in 3-day-old brain is not coincident temporally with the period of myelination (Jacobson, 1963) when lipid synthetic activity is brisk. Maximum incorporation of acetate and palmitate into cerebral cortex lipids occurs in the second postnatal week (Patel and Tonkonow, 1974;Carey, 1975).…”
Section: )mentioning
confidence: 99%